Surgical approaches to canine appendicular osteosarcoma part 2 – limb-sparing techniques - Borges, Ryshely Sonaly de Moura; da Silva, Paloma Helena Sanches; Pimentel, Pedro Antônio Bronhara; Dornas, Renato Pereira; Almendros, Angel; Giuliano, Antonio; Horta, Rodrigo dos Santos; Marinho, Paulo Vinícius Tertuliano (Frontiers in Veterinary Science, 2025)
Osteosarcoma (OSA) is one of the main malignant primary bone neoplasms affecting humans and other vertebrate animals, and it represents the most common bone tumor in dogs, mainly affecting the appendicular skeleton. Given the highly aggressive nature of this cancer and the poor prognosis, immediate surgical intervention is recommended to achieve local control. Surgical treatment options may include radical surgery of the affected limb, considered the standard procedure, or limb preservation in selected cases. The purpose of this narrative literature review is to describe the limb-sparing techniques performed in the treatment of canine appendicular OSA. Limb-preserving techniques may include partial or total scapulectomy, excision of the bone segment with the tumor, and reconstruction using cortical allografts or metal endoprosthesis. Other options may involve endoexoprosthesis, pausterized tumor autografts, roll-over transposition of the ulna, limb shortening, and distraction due to bone transport. Those techniques are satisfactory in maintaining quality of life and may offer a good local disease control if the patient is properly selected, usually at initial stage.